Genome-wide association mapping revealed SNP alleles associated with resistance to cereal cystn nematode (Heterodera filipjevi) in wheat - Majd Taheri, Zahra; Tanha Maafi, Zahra; Nazari, Kumarse; Zaynali Nezhad, Khalil; Rakhshandehroo, Farshad; Dababat, Abdelfattah A.S. (Tarbiat Modares University, 2024)
Resistance traits are economically important in crops in terms of accessibility to promising resistant germplasm. This study was conducted to evaluate SNP marker-trait association for Cereal Cyst Nematode (CCN), Heterodera filipjevi, in a large number of natural bread wheat populations. Phenotypic data analyzed using GLM (Generalized Linear Model) indicated significant differences among the landrace accessions for resistance to H. filipjevi. The genotyping was performed by 152K SNP chip on 188 accessions. After filtering, 10,471 polymorphic SNPs were employed for Genome Wide Association Study (GWAS). Population structure among the wheat genotypes were investigated using 840 well distinct SNP markers. Two sub-populations were revealed by structure software, and eleven markers were found to be significantly (P-value< 0.001) associated with resistance to H. filipjevi on chromosomes 2A, 3B, 4A, 4B, 5A, 5B, 5D, and 6B. The linkage disequilibrium analysis for all significantly associated SNPs showed that markers on chromosomes 4A and 4B were in high intra-chromosomal linkage disequilibrium, and, consequently, eight markers were recommended as strongly associated with resistance to H. filipjevi. The present study demonstrated valuable sources of resistance in the studied wheat genotypes against a widespread and important species of CCNs. The associated markers could be used in molecular breeding programs of bread wheat.